Analisis Spasial Kualitas Air Di Kanal Pampang Kota Makassar (Window of Public Health Journal, 2025)
Environmental pollution is a serious problem that is often found in urban areas, including in Makassar City. One of the affected areas is the Pampang Canal, which serves as the main drainage channel for the surrounding densely populated settlements. Community activities that dispose of domestic waste directly into the canal have led to a decline in water quality and pose potential environmental health risks. This study aims to analyze the spatial conditions of water quality in the Pampang Canal using a non-experimental observational approach, focusing on parameters such as pH, TDS, TSS, and Pb that directly impact water health and are critical indicators for assessing pollution levels. Data collection was conducted through field surveys, which included observations and measurements of several water quality parameters, specifically pH, TDS, TSS, and Pb. Furthermore, the data obtained were analyzed using spatial mapping techniques to describe the distribution of pollution at each sampling point. The study's results show variations in water quality parameter values at several locations, indicating differences in pollution levels along the canal flow. These findings aim to guide local governments and communities in implementing targeted management strategies for the Pampang Canal, with the ultimately goal of improving water quality and environmental health in Makassar City.